New insights into Damarchus: a new species and gynandromorph description from Thailand (Araneae: Bemmeridae) - Kunsete, Chawakorn; Thanoosing, Chawatat; Sivayyapram, Varat; Traiyasut, Prapun; Warrit, Natapot (Zootaxa, 2025)
The genus Damarchus Thorell, 1891, represents a relatively neglected group of mygalomorph spiders distributed across several Asian countries, including India, Indonesia, Malaysia, Myanmar, Singapore, and Thailand. This study describes a new species, Damarchus inazuma sp. nov., discovered in Thailand. The male D. inazuma is identified by the presence of three diminutive spines on the tibial apophysis, whereas the female is characterized by an elongated spermathecal stalk that exhibits an inward curvature. Additionally, we report the identification of a gynandromorph specimen of D. inazuma, marking the first recorded instance of this condition within the family Bemmeridae.